Case of Budd-Chiari syndrome, an enigma as abdominal tuberculosis in a tubercular endemic country: A case report. (October 2022) - Shrestha, Riya; Karki, Saurab; Timilsina, Bibek; Sherpa, Tenzin Norphel; Sapkota, Suhail; Dhakal, Binaya; Kadel, Bijan
Abstract: Introduction and importance: Bud-Chiari syndrome is an uncommon disease due to obstruction of hepatic venous outflow. Clinical manifestations range from asymptomatic cases to those requiring liver transplants. The study highlights the importance of diagnosing a case of Budd-Chiari syndrome which has been suspected with abdominal tuberculosis where anti-tubercular drugs may themselves damage the liver. Case presentation: Herein we report a case of 18 years old female presenting with upper abdominal pain along with recurrent abdominal distention, jaundice, and deranged liver function. Also, adenosine deaminase level was raised in both pleural and peritoneal fluids, hence, anti-tubercular treatment was started but could not be continued as she developed adverse reactions to these drugs. CT scan later revealed features suggestive of Budd-Chiari syndrome. Initially, she was managed with balloon angioplasty, but her condition worsened ultimately requiring a liver transplant. Clinical discussion: Budd Chiari syndrome can present with subtle presentation and since abdominal tuberculosis is very non-specific, the two conditions can be very confusing, particularly in the tubercular endemic region. Detailed clinical assessment along with proper investigations and imaging should be performed for early recognition as both conditions are associated with high morbidity and mortality if not treated timely. Conclusion: The necessity of careful investigation and consideration of Budd-Chiari syndrome as an important cause of ascites with jaundice and deranged liver function in TB endemic regions along with early anticipation of liver transplant is necessary, as in this case. Highlights: Budd-Chiari syndrome is an uncommon disease due to obstruction of hepatic venous outflow. Associated ascites and pleural effusion in a tuberculosis endemic condition can be confused with tuberculosis. Liver transplant can be ultimately required at later stage.